The Ca-activated Cl channel and its control in rat olfactory receptor neurons - Reisert, Johannes; Frings, Stephan (The journal of general physiology, 2003)
Odorants activate sensory transduction in olfactory receptor neurons (ORNs) via a cAMP-signaling cascade, which results in the opening of nonselective, cyclic nucleotide-gated (CNG) channels. The consequent Ca2+ influx through CNG channels activates Cl channels, which serve to amplify the transduction signal. We investigate here some general properties of this Ca-activated Cl channel in rat, as well as its functional interplay with the CNG channel, by using inside-out membrane patches excised from ORN dendritic knobs/cilia. At physiological concentrations of external divalent cations, the maximally activated Cl current was ∼30 times as large as the CNG current. The Cl channels on an excised patch could be activated by Ca2+ flux through the CNG channels opened by cAMP. The magnitude of the Cl current depended on the strength of Ca buffering in the bath solution, suggesting that the CNG and Cl channels were probably not organized as constituents of a local transducisome complex. Likewise, Cl channels and the Na/Ca exchanger, which extrudes Ca2+, appear to be spatially segregated. Based on the theory of buffered Ca2+ diffusion, we determined the Ca2+ diffusion coefficient and calculated that the CNG and Cl channel densities on the membrane were ∼8 and 62 μm−2, respectively. These densities, together with the Ca2+ diffusion coefficient, demonstrate that a given Cl channel is activated by Ca2+ originating from multiple CNG channels, thus allowing low-noise amplification of the olfactory receptor current.